From discrete complex to 1-D coordination polymer by subtle variation of ligand donor: structures and electrical conductivities. Issue 11 (2nd July 2016) - Wu, Jun-Xi; Zhou, Dong-Dong; Zhang, Chi; Zhou, Hao-Long; Zhang, Jie-Peng
Abstract: A new coordination compound, [Cu(sphen)] (Hsphen = 2-sulfydryl-1, 10-phenanthroline), as an analog of [Cu(ophen)] (Hophen = 1 H -[1, 10]phenanthrolin-2-one), is synthesized and characterized by single-crystal X-ray diffraction. While [Cu(ophen)] is a planar discrete complex showing strong π – π stacking, [Cu(sphen)] is further connected by Cu–S bonds to form a one-dimensional coordination polymer. The bulk electrical conductivity of [Cu(sphen)] (5.0 × 10 −3  S·cm −1 ) is ~3 orders of magnitude higher than that of [Cu(ophen)] (3.9 × 10 −6  S·cm −1 ). Abstract :